The Green Production Strategy for the Small and Medium Size Enterprises of The Leather Sandal - Issa Dyah Utami; Ika Deefi Anna; Wulan Puspitasari (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Green production is closely related to sustainable development. The SMEs of sandal artisans who use leather raw materials for production processes with a green production perspective must manage leather raw materials and waste not to damage the environment. This paper aims to identify strategies to increase green production in leather sandal artisans’ SMEs using the K-Means Cluster and Analytical Hierarchy Process Method. This research found that the best alternative strategy recommended is the evangelist strategy, a fundamental change in SMEs to protect the environment.